Synthesis, Characterization and Biological Activity of Complexes of N-phenyl-N’-(2-pyrimidyl) Thiourea with Pd(II), Pt(II), Ni(II), Co(II),Cu(II), Mn(II), Cd(II) and Zn(II) - H. ABDULLAH, BAYAZEED (Asian Journal of Chemistry, 2010)
This paper reports the synthesis, characterization and biological activities of Pd(II), Pt(II), Ni(II), Co(II), Cu(II), Mn(II), Cd(II) and Zn(II) complexes with N-phenyl-N'-(2-pyrimidyl) thiourea (PPTU). All the synthesized complexes were characterized by elemental analysis, infrared and electronic spectral data, magnetic susceptibility and molar conductance. The biological activity of the synthesized complexes were tested against Staphylococcus aures, Escherichia coli and Pseudomonas aeruginosa using a well assay method. Dunnett method was used to compare the biological activities of the complexes with the control.